2004
DOI: 10.1007/s10340-004-0055-4
|View full text |Cite
|
Sign up to set email alerts
|

Mating disruption of the pink bollworm Pectinophora gossypiella (Saund.) (Lepidoptera: Gelechiidae) using gossyplure PB-rope dispensers in cotton fields

Abstract: The effects of mating disruption on population densities and percentage of damage of the pink bollworm Pectinophora gossypiella (Saunders) were investigated in a cotton field in central Greece, in 1992 and. A 10-ha field was divided in two parts of 5 ha each. PB-rope dispensers were installed in midseason in one part, whereas the other was used as a control field. Catches of pink bollworm moths in pheromone-baited traps and damage caused were recorded in both the treated and control fields. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
0
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
5
0
0
Order By: Relevance
“…Population of pest was less in treated plot as compared to control. Our findings are in line with the findings of other researchers (Lykouressis et al, 2004).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Population of pest was less in treated plot as compared to control. Our findings are in line with the findings of other researchers (Lykouressis et al, 2004).…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are similar with findings of early researchers (Solangi et al, 2005). PB-ropes were installed against Pectinophora gossypiella to check mating disruption on population its densities (Lykouressis et al, 2004). Population of pest was less in treated plot as compared to control.…”
Section: Discussionsupporting
confidence: 90%
“…Sufficient gossyplure for reducing moth catches in traps was present in pheromone dispensers even after 90 days. Our findings are also similar to the study of Lykouressis et al (2004) who observed the mating disruption effects on population dynamics and percentage of damage caused by pink bollworm. The results revealed that moth catches were highly reduced in the treated fields and mid-season installation of dispensers was successful.…”
Section: Discussionsupporting
confidence: 92%
“…Only the Ulala, Ulala+buprofezin and Polo were applied during the whole cropping season of cotton for sucking pests. Our results agreed with Lykouressis et al (2004) who applied PB rope dispensers in cotton field and observed that population of pink bollworm reduced effectively and populations of other cotton pests, such as whiteflies and aphids, were also reduced in those experiment areas. Similar observations were recorded by Lykouressis et al (2005) who conducted experiment and the one field was applied with PB ropes and in the other insecticide was applied.…”
Section: Discussionsupporting
confidence: 91%